Praktek Persekongkolan Tender Dalam Proses Penjualan Saham (Analisa Hukum Persaingan Usaha Tidak Sehat Kasus Penjualan Saham PT. Indomobil International, Tbk) - Kurniasari, Tri Widya (PASAI, 2013)
At the end of 2001, Badan Penyehatan Perbankan Nasional (BPPN) trough PT.Holdiko Perkasa sold PT.Indomobil Sukses International, Tbkâs shares. However, in the process of shares purchase there is a presumption of the collusion between PT.Holdiko Perkasa as the purchase tender organizer with PT.Cipta Sarana Duta Perkasa as the tender winner which caused this country lost hundred billion rupiahs. This research is using the qualitative methode, not only with the document and the policy study but also in depth interview with the people who are directly involved in this case. Therefore, this research attempts to analyze if there was any violation of Article 22 the Act Number 5 of 1999 regarding Prohibition of Monopolistic Practices and Unfair Business Competition. The Supreme Courtâs verdict as the final finishing case could be the law reference for the same cases. Not only that, this verdict also showed us that we must make the revision to the whole of our policies, especially in the business sector in order to creating a conducive and fair economical condition in the country.Â